Estrutura organizacional do tipo network e a satisfação no trabalho - Magalhães, Rogério Oliveira de (1999)
As per many historians, we are now moving into a new era, that of knowledge and information, the digital era. In our new global environment, we witness the advent of two strategic weapons with which organizations will be competing in the forthcoming twenty-first century: creativity and integration. Along with these newfound resources, companies are also tapping into a network-type organizational structure that should, in turn, enable them to manage creativity and integration. Such kind of structure is not concerned with new ways of manipulating subordinates to one's advantage. Instead, it challenges us to rethink the basics: our values, attitudes and assumptions about leadership, work and time. Conventional steep hierarchies, with their all-pervading bureaucracy, are simply not endowed with the agility required to respond to shifting market needs, as observed today. People specialize in narrow activities, missing the full significance of their work, deprived of genuine intrinsic motivation. With the growing awareness that people constitute a company's most valuable asset, demotivation may very well spell disaster for the future of those businesses that refuse to take heed. As such, it is now essential that management acknowledge the reciprocity upon which company-individual relationships are based. The purpose of this dissertation is to analyze how the human factor impinges upon the work performed within a network structure, by relating the underpinnings of the network organizational model to human needs, and demonstrating the correlation that exists between job satisfaction and organizational structures grounded on creativity and integration. We begin with a review of existing literature, as perceived from three distinct angles. First, we explain how changes in the world today are affecting company strategies. Second, we describe the impact of the twentyfirst century strategy inside organizations. And finally, we focus on the psychological facet of people, their needs, such as autonomy, competence and interpersonal relationships, as well as the intrinsic and extrinsic factors that contribute to their satisfaction. This review thus enabled us to assess the impact of the network organizational structure on employee motivation. We then present the project for a pilot study on those factors that most contribute to people's satisfaction, confirming the important role played by intrinsic factors. We also demonstrate that satisfaction rates are directly affected by the work environment, varying in accordance with the degree of autonomy that employees enjoy. Finally, we put forth our conclusions and some practical recommendations for internai organizational changes, along with the costs that they will entail, and how they should be managed over the long term.